Hubungan Tingkat Gaya Hidup Hedonisme terhadap Perilaku Seksual pada Remaja Kelas XI di SMK Bakti Purwokerto: THE CORRELATION BETWEEN HEDONISTIC LIFESTYLE LEVEL AND SEXUAL BEHAVIOR IN GRADE XI ADOLESCENTS (STUDENTS) AT SMK BAKTI PURWOKERTO - Shanya Gupita Rahmadhenta; Wulan Margiana (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2023)
Sexual behavior in adolescents is closely related to modern lifestyles and tends to violate the rules. For example, they will spend their free time doing negative things such as somking, coming home late to have fun, getting drunk, taking drugs, and accessing pornography. The phenomenon and desire for free sex inadolescents occurs in the form of pornography films by 97%, kisses, caresses and oral sex by 93.7%, 62.7% of junior and senior high school teenagers are no longer virgins, and 21.2% of them do abortion. According to the 2019 Program Accountability Performance Survey, in Central Java Province, around 1.9% of boys and 0.4% of girls had sex before marriage. The study aims to analyze the correlations between the level of hedonism lifestyle and sexual behavior in grade XI adolescents at SMK Bakti Purwokerto. This research used quantitative analytic correlative method with a cross sectional design approach. The sample technique used is a total sampling technique with the number of respondents being 127 students of grade XI. The analysis of this study used univariate analysis in the form of frequency distribution and bivariate analysis using Spearman rho test.The research results show that r = 0.86 and a significance coefficient of 0.000 < 0.05 there is a significant correlation between the level of hedonistic lifestyle and sexual behavior in grade XI adolescents at SMK Bakti Purwokerto.